A Multiscale View of the Mechanisms Underlying Ketamine’s Antidepressant Effects: An Update on Neuronal Calcium Signaling - Kawatake-Kuno, Ayako; Murai, Toshiya; Uchida, Shusaku (Frontiers in Behavioral Neuroscience, 2021)
Major depressive disorder (MDD) is a debilitating disease characterized by depressed mood, loss of interest or pleasure, suicidal ideation, and reduced motivation or hopelessness. Despite considerable research, mechanisms underlying MDD remain poorly understood, and current advances in treatment are far from satisfactory. The antidepressant effect of ketamine is among the most important discoveries in psychiatric research over the last half-century. Neurobiological insights into the ketamine’s effects have shed light on the mechanisms underlying antidepressant efficacy. However, mechanisms underlying the rapid and sustained antidepressant effects of ketamine remain controversial. Elucidating such mechanisms is key to identifying new therapeutic targets and developing therapeutic strategies. Accumulating evidence demonstrates the contribution of the glutamatergic pathway, the major excitatory neurotransmitter system in the central nervous system, in MDD pathophysiology and antidepressant effects. The hypothesis of a connection among the calcium signaling cascade stimulated by the glutamatergic system, neural plasticity, and epigenetic regulation of gene transcription is further supported by its associations with ketamine’s antidepressant effects. This review briefly summarizes the potential mechanisms of ketamine’s effects with a specific focus on glutamatergic signaling from a multiscale perspective, including behavioral, cellular, molecular, and epigenetic aspects, to provide a valuable overview of ketamine’s antidepressant effects.